Immigrants from Eastern Partnership (EaP) Countries in Spain - Lídia Farré; Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2013)
Most EaP migrants in Spain come from Ukraine, followed by, to a much lesser extent, Moldavia, Armenia, and Georgia. Relative to other migrants, they are those who most recently arrived to Spain. Despite being considerably more educated than natives and other migrants, they are less likely to work than natives and other migrants upon arrival to Spain. Using data from Spanish Labor Force Survey (LFS) from the years 2000 to 2011, this paper analyzes how their employment situation evolves with time in Spain, the type of sectors they work in, and their welfare use, including unemployment insurance receipt.
Keywords: J15; J24; J61; J62; 330; immigrants' employment and welfare assimilation